Spatial Analysis of Lymphatic Filariasis Case and Mosquito Resting Place in Rural Area of Brebes Regency, Indonesia - Siwiendrayanti, Arum; Anggoro, Sutrisno; Nurjazuli, Nurjazuli (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Brebes Regency is an endemic area of Lymphatic Filariasis (LF) and has the highest number of LF cases in Central Java Province, Indonesia. Despite it is located in the coastal region, which is already known as one of the risk factors of LF, the LF case is distributed more in rural areas, away from the shoreline. Adult mosquitoes need a particular site, called a resting place, to rest after and before biting for a blood meal. The purpose of this study was to analyze spatially the distribution of LF cases and mosquito resting places in three subdistricts whose highest LF case is in the Brebes Regency. The three subdistricts are rural areas. The observed resting places were cattle pens, unmaintained bushes, and maintained bushes. The data of LF patients were obtained from the Health Office of Brebes Regency, which stood at 14 patients. Spatial mapping of LF case and mosquito resting place distribution was composed. 4 patients were located in the mosquito flight radius from unmaintained bushes, 3 patients were located in the mosquito flight radius from cattle pen, and 7 patients were located in the mosquito flight radius from both unmaintained bushes and cattle pen. It indicated unmaintained bushes, together with cattle pen, are the favorable resting place contributing to LF transmission.